2022
DOI: 10.1629/uksg.559
|View full text |Cite
|
Sign up to set email alerts
|

Exploring open access coverage of Wikipedia-cited research across the White Rose Universities

Abstract: The popular online encyclopaedia Wikipedia is an important and influential platform that assists with the communication of science to a global audience. Using data obtained from Altmetric.com and Unpaywall, we looked at research from the White Rose Universities (Sheffield, Leeds and York) that is cited on Wikipedia. Of that research, we explored what percentage of citations were available open access (OA) and the location of those citations to ascertain whether they were hosted by publishers or within OA repos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…As Tattersall et al (2022) pointed out, "it is noteworthy that Wikipedia plays a unique role in the information ecosystem as a bridge between informal discussion and academic publishing". For example, during the COVID-19 pandemic, WHO (2020) worked with the Wikimedia foundation to expand public access to the latest and most reliable information about the virus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Tattersall et al (2022) pointed out, "it is noteworthy that Wikipedia plays a unique role in the information ecosystem as a bridge between informal discussion and academic publishing". For example, during the COVID-19 pandemic, WHO (2020) worked with the Wikimedia foundation to expand public access to the latest and most reliable information about the virus.…”
Section: Resultsmentioning
confidence: 99%
“…As Tattersall et al. (2022) pointed out, “it is noteworthy that Wikipedia plays a unique role in the information ecosystem as a bridge between informal discussion and academic publishing”.…”
Section: Resultsmentioning
confidence: 99%
“…Since its launch in 2001, perceptions of Wikipedia have evolved [24]. Although it is not universally accepted [25], academics, health professionals, and librarians have acknowledged its influence and popularity for the communication of science [26][27][28][29] and public health education [23,[30][31][32], despite a limited understanding of how or why readers engage with it [33,34]. Scholarship has explored the benefits associated with including the citation rate on Wikipedia in assessments of the reach of published works [35] and contributing to Wikipedia has continued to gain popularity in medical education [36][37][38][39][40].…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…They found that only 357 of 1,350 reputable journals are cited at least once in the entire Wikipedia, not well-cited across psychology-related Wikipedia entries but also well-cited across the whole of Wikipedia. Tattersall et al (2022) extracted 6,454 citations of White Rose Universities' Research on Wikipedia from 1922 to 2019 from Altmetric.com and Unpaywall Application Programming Interface (API). According to Wikipedia, the highest citations occurred in life, medical and health sciences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tattersall et al (2022) extracted 6,454 citations of White Rose Universities' Research on Wikipedia from 1922 to 2019 from Altmetric.com and Unpaywall Application Programming Interface (API). According to Wikipedia, the highest citations occurred in life, medical and health sciences.…”
Section: Literature Reviewmentioning
confidence: 99%